(3TQM OjhGf GdMeGSI dCHi JeGes - (3CHh GdMSjf CMeO Hf aGQS Hf RcQjG GdQGRis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3BNQgG (B:s
(3jfJgi Edi BNQ TQM bhd Sdei Hf QHjYI MdJ JeGVQ ZQHg aCNdJ s
(3cJHJ HQSe GdNRGfI GdSWGfjI GdehdhjI GdedcjI GdXGaQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B421 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B488 s
(3eUOQ GbJfGA GdCUd (B:s
(3dGdg di (B(1716) s
Keywords: (3GdCOHs